Tri - Dević, Goran (Croatia : Factum Documentary Film Project, 2007)
“Do we still need to keep talking about the war?" is the motto of this documentary by Goran Dević, who has decided to conduct confessional interviews with three men actively involved in the conflict in the former Yugoslavia. Serb Novica Kostić tried his best to avoid conscription but failed. During the war he was wounded and he now recalls how easily a person can be turned into a "killing machine." Rough-edged and slightly cynical Croat Narcis Misanović joined up voluntarily and was convicted after the war of the murder of 16 Serb civilians. Ivica Petrić saw his father and brother killed in front of his eyes. At the age of 11 he was already working in a military canteen and a few years later was fighting in the ranks of the Bosnian army. These interviews, recorded during car journeys, bring the fratricidal conflict home to the viewer. Even though the three fought on different sides, they all agree that the war was inhumane and absurd, and that today everybody behaves as if nothing happened.
Verzio Film Festival Submission
Duration: 00:30:00
Verzio Film Festival Submission
Keywords: Documentary films